A candidal oesophageal stricture responsive to fluconazole therapy. Issue 1 (1st June 2013) - Kalla, Rahul; Kaushik, Vishal
Abstract : We report a case of candidal oesophageal stricture in an 81 year-old man with a 2 year history of gradual onset dysphagia and odynophagia to solids. Although rare, most cases have reported treatment success with oesophageal balloon dilation. We report the first case of candidal oesophageal stricture resolution with a prolonged course of anti-fungal therapy.